Mekanisme Internal Tata Kelola Korporasi dan Pengungkapan Perubahan Iklim - Yuliantama, Fauzan Rizki; Sary, Putri Maya; Ayunda, Shafa; Rahayu, Raisya Aprilia; Zaitul, Zaitul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
As global awareness of climate change grows, corporate transparency becomes increasingly crucial, yet little research has addressed the role of corporate governance in climate change disclosure. The purpose of this study is to analyze the relationship between various corporate governance mechanisms and the extent to which companies disclose climate change-related information. A quantitative research method was employed, utilizing secondary data from the financial reports of 11 pharmaceutical companies in Indonesia, selected through purposive sampling. The study used multiple linear regression analysis to evaluate the effects of governance variables on climate change disclosure. The results revealed that the gender, nationality, and size of the Board of Commissioners significantly influence climate change disclosure. However, the size of the Board of Commissioners, the independence of the Board of Commissioners, the age of the Board of Commissioners, and the level of education of the Board of Commissioners did not show any significant effect on climate change disclosure. The findings suggest that certain characteristics of corporate governance, particularly gender diversity, nationality, and company size, play an essential role in enhancing climate change disclosure. These results have important implications for policymakers, companies, and stakeholders in promoting greater transparency regarding climate-related risks.